2021
DOI: 10.1016/j.jaad.2020.08.127
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab shows long-term effectiveness in a large cohort of treatment-refractory atopic dermatitis patients in daily practice: 52-Week results from the Dutch BioDay registry

Abstract: M. S. (2021). Dupilumab shows long-term effectiveness in a large cohort of treatment-refractory atopic dermatitis patients in daily practice: 52-Week results from the Dutch BioDay registry, Journal of the American Academy of Dermatology, 84(4), e279-e280.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 30 publications
9
77
2
Order By: Relevance
“…Our study found low discontinuation rates of dupilumab treatment (1.8%). This percentage of discontinuation is lower compared to the multicentre cohort of Ariëns et al (8.1%) and retrospective daily practice study of Jo et al (12%) [6,12].…”
Section: Commentarycontrasting
confidence: 53%
See 3 more Smart Citations
“…Our study found low discontinuation rates of dupilumab treatment (1.8%). This percentage of discontinuation is lower compared to the multicentre cohort of Ariëns et al (8.1%) and retrospective daily practice study of Jo et al (12%) [6,12].…”
Section: Commentarycontrasting
confidence: 53%
“…In our cohort, new-onset conjunctivitis was observed in 9.69% of patients, in accordance with the literature. The reported incidence in clinical trials and in real-life studies ranges from 5% to 28%, and from 6% to 62% of dupilumab-treated patients, respectively [3,4,6,11]. Regarding other AEs, we observed a lower incidence of red face and no case of arthralgia, reported by Kreeshan et al in 10 and 6 patients, respectively.…”
Section: Commentarysupporting
confidence: 48%
See 2 more Smart Citations
“…18 years) who had been treated with dupilumab were eligible for the current study when they had been treated between 16 and 52 weeks at inclusion. This group was included because a steady state concentration of dupilumab from 16 weeks has been reported (7)(8)(9). On the 10th of April 2020, a digital questionnaire was sent to eligible patients, using Castor Electronic Data Capture (10).…”
Section: Study Design Population and Recruitmentmentioning
confidence: 99%